Diet and feeding selectivity of the Andean Flamingo Phoenicoparrus andinus and Chilean Flamingo Phoenicopterus chilensis in lowland wintering areas - Polla, Wanda (2018)
Flamingos Phoenicopteridae sp. are gregarious birds that travel long distances between breeding and feeding sites. Here we describe the diet and feeding selectivity of two flamingo species, the Andean Flamingo Phoenicoparrus andinus and Chilean Flamingo Phoenicopterus chilensis, which coexist in a lowland area of Argentina. Environmental characteristics and available food resources were assessed at twelve lakes where feeding flocks of both species of flamingos occurred. Food items found in faeces (16S rRNA for bacteria and archaea) and microscopic analyses (for Cyanobacteria, microalgae and microinvertebrates) were analysed, and the birds? feeding selectivity and niche overlap were estimated. Results showed that the lakes were of eutrophic to hypereutrophic status, and with hypohaline to mesohaline salinity levels. Predominant microorganisms belonged to the Planctomycetes, Verrucomicrobia, Chloroflexi, Euryarchaeota, Cyanobacteria, Bacillariophyta and Copepoda phyla. Euryarchaeota and Firmicutes were the main phyla found in the faeces, with Chloroflexi and Planctomycetes also present in smaller quantities. Proteobacteria were well represented in Andean Flamingo faeces, but Verrucomicrobia were scarce in both species. Cyanobacteria, Bacillariophyta, Copepoda, Cladocera, and Rotifera were abundant in Chilean Flamingo faeces, and larger organisms belonging to Ostracoda, Nematoda, and Diptera were also found. The most consumed taxa were in the intermediate to large size range (104 to 2×105 μm3, and 108 to 2×108 μm3). Andean Flamingo faeces were composed mainly of microalgae, especially diatoms. Cladocera and Copepoda species were found to a lesser extent, showing the flamingos? preference for intermediate prey sizes (104 to 2×105 μm3). Food selection was probably dependent on the spatial variability in prey availability, as both positive selectivity (for Bacillariophyceae) and avoidance (for Copepoda) were observed in Chilean Flamingos. In contrast, Andean Flamingos showed a high positive selection for diatoms, and strong negative selection for microinvertebrates. Both flamingo species can apparently coexist whilst feeding on a wide spectrum of microorganisms, but trophic niches differed in the amounts of Cyanobacteria, microalgae and microinvertebrates taken. Such a low niche overlap probably contributes to the coexistence of both sympatric species in similar waters.